Physical and Chemical Characteristics of Mosquito Larvae Nesting Sites in Belang District, Southeast Minahasa Regency - Nachda, Andi Agista (CV. Publikasi Indonesia, 2025)
This study aims to evaluate the implementation of the parking fee policy on public roads in Kudus city and to identify the factors inhibiting its successful execution. The study uses a qualitative research approach and applies Merilee S. Grindle’s theory, which focuses on two indicators: policy content and the context of implementation. Data were collected through interviews with key stakeholders, including local government officials, parking attendants, and the public. The findings reveal that the policy’s implementation is facing significant challenges, primarily due to the persistence of illegal parking practices and the involvement of unauthorized parking attendants in the city. These issues have undermined the intended outcomes of the parking fee policy, preventing it from achieving its full potential in regulating traffic and generating revenue for public services. The study also highlights factors such as inadequate enforcement mechanisms, insufficient public awareness, and limited coordination between local authorities and enforcement agencies. Based on these findings, it is recommended that the local government strengthen law enforcement, improve public education on the benefits of the policy, and increase collaboration with stakeholders to ensure more effective implementation of the parking fee policy. The research contributes to the understanding of urban policy challenges in managing public resources and offers practical insights for local governments seeking to implement similar policies in urban areas.